NEAR VISION OUTCOME IN PATIENTS WITH AGE-RELATED MACULAR DEGENERATION TREATED WITH AFLIBERCEPT. Issue 9 (September 2016) - Epstein, David; Amrén, Urban
Abstract : Purpose: The aim of this study was to investigate the outcome in near vision and the best-corrected visual acuity in patients with wet, age-related macular degeneration treated with aflibercept in a fixed bimonthly regimen in an ordinary clinical setting. Methods: The study was a retrospective, nonrandomized consecutive case series including 85 patients with wet, age-related macular degeneration followed for 18 months. During the first year all the patients received aflibercept injections in a fixed regimen at the following time points: Month 0, 1, 2, 4, 6, 8, 10, and 12. From Month 12 to Month 18, patients were treated with a treat and extend algorithm. Results: The median near visual acuity improved from 12 points (95% confidence interval [CI] 10.5–13.4) at baseline to 5 points both at Month 12 (95% CI 3.8–6.2) and at Month 18 (95% CI 3.6–6.4) ( P < 0.0001). At the 18-month visit, 58% (42/73) of the patients had a near visual acuity of at least 5 points compared with 7% (6/85) ( P < 0.0001) at baseline. Best-corrected visual acuity improved from 60.9 letters (Snellen 20/63) (95% CI 58.4–63.4) at baseline to 68.1 letters (20/40) (95% CI 65.3–70.9) ( P < 0.001) at Month 12 and 69.6 letters (20/40) (95% CI 66.7–72.5) ( P < 0.001) at Month 18. Conclusion: Significant improvements were found in near vision and best-corrected visual acuity. The improvement in near vision was comparably greater than the change in best-corrected visual acuity. Monitoring near vision can contribute additional information when managing the patient with wet, age-related macular degeneration. Abstract : Significant improvement was found in near vision when treating patients with aflibercept in wet AMD in a fixed bimonthly regimen. The improvement in near vision was comparably greater than the change in BCVA. Monitoring near vision can contribute additional information when managing the patient with wet AMD.